Problématiser et modéliser le quartier durable par une enquête interdisciplinaire au temps de l’Anthropocène à l’école secondaire : quel espace interprétatif partagé entre divers acteurs sociaux ? - Patrick Roy; Delphine Schumacher; Helene Kolly (Éducation et Socialisation)
A discursive community of professional practices has engaged a collective of actors in French-speaking Switzerland from different social worlds (professors of disciplinary didactics, architects, engineers, secondary school teachers, etc.) in the design of teaching-learning situations and a continuing education device on the sustainable neighborhood apprehended as an object of education in responsible technological innovation. This article explores the potential of this participatory research device, mediated and instrumented by a system of cultural and semiotic tools, to build a shared interpretative space on teaching this complex object by combining the requirements of a STEAM education with those of an anthropocene education. An analysis of discursive interactions between actors over 15 sessions coupled with classroom situations was carried out on three scales of granularity (macroscopic-mesoscopic-microscopic). The results show that, while the actors are engaged in constructing a shared interpretative space on the conduct of an interdisciplinary investigation articulating problematization and modeling while integrating the technical design process, the dimension of politics remains on the margins of the teaching-learning situations implemented in the classrooms.